Common Hazards Associated with Sheep and Goat Feed - Chalise Brown; Diwakar Vyas; Jason M. Scheffler (EDIS)
This 7-page document provides a list of common hazards to consider in the manufacturing of feed for small ruminants. Written by Chalise Brown, Diwakar Vyas, and Jason M. Scheffler, and published by the UF/IFAS Department of Animal Sciences, November 2020.